Pengaruh Brand Image dan Celebrity Endorser terhadap Keputusan Pembelian di Arascarf Malang (Jurnal Manajemen Kreatif dan Inovasi, 2025)
Thislresearchlwas a quantitativelresearch with two independentlvariables, namely Brand Image (X1) and Celebrity Endorser (X2) and a dependent variable, Purchase Decision (Y). The data collection method used was conducted by distributing questionnaires to 100 Arascaraf consumer respondents who bought Arascraf products. The sampling technique used in this research was purposive sampling. The data analysis of this study used multiple linear regression and hypothesis testing. The results showed that the Brand Image and Celebrity Endorser had a partial and simultaneous positive influence on the purchasing decisions of 77.8% and the remaining 22.2% was influenced by other factors. While the variable that had a dominant influence on Consumer Purchase Decisions was the Brand Image variable with a regression coefficient value of 0.866. Based on the results of the study, it can be concluded that Brand image and Celebrity Endorser are the reasons for Arascraf consumers to make purchasing decisions at Arascraf.